The road to the synthesis of "difficult peptides". (27th November 2015) - Paradís-Bas, Marta; Tulla-Puche, Judit; Albericio, Fernando
Abstract : This review provides an extensive range of methodologies which outline the path to achieve the synthesis of "difficult peptides". Abstract : The last decade has witnessed a renaissance of peptides as drugs. This progress, together with advances in the structural behavior of peptides, has attracted the interest of the pharmaceutical industry in these molecules as potential APIs. In the past, major peptide-based drugs were inspired by sequences extracted from natural structures of low molecular weight. In contrast, nowadays, the peptides being studied by academic and industrial groups comprise more sophisticated sequences. For instance, they consist of long amino acid chains and show a high tendency to form aggregates. Some researchers have claimed that preparing medium-sized proteins is now feasible with chemical ligation techniques, in contrast to medium-sized peptide syntheses. The complexity associated with the synthesis of certain peptides is exemplified by the so-called "difficult peptides", a concept introduced in the 80's. This refers to sequences that show inter- or intra-molecular β-sheet interactions significant enough to form aggregates during peptide synthesis. These structural associations are stabilized and mediated by non-covalent hydrogen bonds that arise on the backbone of the peptide and—depending on the sequence—are favored. The tendency of peptide chains to aggregate is translated into a list of common behavioral features attributed to "difficult peptides" which hinder their synthesis. In this regard, this manuscript summarizes the strategies used to overcome the inherent difficulties associated with the synthesis of known "difficult peptides". Here we evaluate several external factors, as well as methods to incorporate chemical modifications into sequences, in order to describe the strategies that are effective for the synthesis of "difficult peptides". These approaches have been classified and ordered to provide an extensive guide for achieving the synthesis of peptides with the aforementioned features.